2017
DOI: 10.1111/afe.12224
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of potential hybridization in the Thaumetopoea pityocampa‐wilkinsoni complex

Abstract: 1 The winter pine processionary moth complex includes some major defoliating insects of Pinus and Cedrus forests in southern Europe and the Mediterranean Basin, where they also cause health problems to humans and animals. 2 The complex includes at least two species that were separated recently based on molecular and morphological evidence: Thaumetopoea pityocampa in the west and Thaumetopoea wilkinsoni in the east of the Mediterranean Basin. 3 Individuals from two populations, selected as representative of Th.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Such a difference in duration has been interpreted as a way to optimize the larval development in the next generation (Démolin, 1969; Robinet, Laparie & Rousselet, 2015). The duration of this pupal diapause appears genetically determined, as populations from different elevations or latitudes reared under the same conditions over a few generations maintain their typical phenology (Petrucco-Toffolo et al, 2018). Moths generally emerge in summer, but a variable fraction of the individuals may postpone their emergence and enter a prolonged pupal diapause that may last, as far as we know, up to 9 years in Th.…”
Section: Introductionmentioning
confidence: 99%
“…Such a difference in duration has been interpreted as a way to optimize the larval development in the next generation (Démolin, 1969; Robinet, Laparie & Rousselet, 2015). The duration of this pupal diapause appears genetically determined, as populations from different elevations or latitudes reared under the same conditions over a few generations maintain their typical phenology (Petrucco-Toffolo et al, 2018). Moths generally emerge in summer, but a variable fraction of the individuals may postpone their emergence and enter a prolonged pupal diapause that may last, as far as we know, up to 9 years in Th.…”
Section: Introductionmentioning
confidence: 99%
“…As for the activity of T. embryophagum, it is more important after the host population's peak where its regulatory effect is significant, although the number of parasitized egg masses remains low. Petrucco-Toffolo et al [59] attribute this constraint to the protective scales that hinder the parasitic success. However, the results of Daniel et al [60] have reported an abundance of this species in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…First, mean realized fecundity of the host is also lower at the southern edge of the range than at higher latitudes, likely because lower plant quality for larvae associated with hot and dry conditions (Pimentel et al ., 2010); this results in a reduced availability of eggs per egg batch, which may limit the access of the parasitoids to the resources (Mills & Getz, 1996). Second, egg batches from the southern populations of the pine processionary moth are characterized by a different type of scales covering the eggs (Petrucco‐Toffolo et al ., 2018), which may negatively affect the activity of the egg parasitoids that are known to respond to the quality of the eggs (Zovi et al ., 2008; Uemura et al ., 2019). Third, the climate at the southern edge of the range can make it difficult for parasitoids to exploit the resources, because of a bad synchronization between parasitoid emergence and moth oviposition (Auger‐Rozenberg et al ., 2015) or because of a higher probability to be exposed to excessively high temperatures.…”
Section: Discussionmentioning
confidence: 99%